Measurements of mixed harmonic cumulants in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Pachmayer, Yvonne C.; et al. (Physics letters, 2021)
Correlations between moments of different flow coefficients are measured in Pb-Pb collisions at sNN=5.02 TeV recorded with the ALICE detector. These new measurements are based on multiparticle mixed harmonic cumulants calculated using charged particles in the pseudorapidity region |η|<0.8 with the transverse momentum range 0.2<pT<5.0 GeV/c. The centrality dependence of correlations between two flow coefficients as well as the correlations between three flow coefficients, both in terms of their second moments, are shown. In addition, a collection of mixed harmonic cumulants involving higher moments of v2 and v3 is measured for the first time, where the characteristic signature of negative, positive and negative signs of four-, six- and eight-particle cumulants are observed, respectively. The measurements are compared to the hydrodynamic calculations using iEBE-VISHNU with AMPT and TRENTo initial conditions. It is shown that the measurements carried out using the LHC Run 2 data in 2015 have the precision to explore the details of initial-state fluctuations and probe the nonlinear hydrodynamic response of v2 and v3 to their corresponding initial anisotropy coefficients ε2 and ε3. These new studies on correlations between three flow coefficients as well as correlations between higher moments of two different flow coefficients will pave the way to tighten constraints on initial-state models and help to extract precise information on the dynamic evolution of the hot and dense matter created in heavy-ion collisions at the LHC.
Available online 11 May 2021
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
ALICE Collaboration: S. Acharya, V. Anguelov, F. Antinori, P. Antonioli, C. Anuj, N. Apadula, L. Aphecetche, H. Appelshäuser, S. Arcelli, R. Arnaldi, I.C. Arsene, M. Arslandok, A. Augustinus, R. Averbeck, S. Aziz, M.D. Azmi, A. Badalà, Y.W. Baek, X. Bai, R. Bailhache, Y. Bailung, R. Bala, A. Balbino, A. Baldisseri, M. Ball, D. Banerjee, R. Barbera, L. Barioglio, M. Barlou, G. G. Barnaföldi, L. S. Barnby, V. Barret, C. Bartels, K. Barth, E. Bartsch, F. Baruffaldi, N. Bastid, S. Basu, G. Batigne, B. Batyunya, D. Bauri, J.L. Bazo Alba, I.G. Bearden, C. Beattie, I. Belikov, A.D.C. Bell Hechavarria, F. Bellini, R. Bellwied, S. Belokurova, V. Belyaev, G. Bencedi, S. Beole, A. Bercuci, Y. Berdnikov, A. Berdnikova, D. Berenyi, L. Bergmann, M.G. Besoiu, L. Betev, P.P. Bhaduri, A. Bhasin, I. R. Bhat, M.A. Bhat, B. Bhattacharjee, P. Bhattacharya, L. Bianchi, N. Bianchi, J. Bielčík, J. Bielčíková, J. Biernat, A. Bilandzic, G. Biro, S. Biswas, J. T. Blair, D. Blau, M.B. Blidaru, M.C. Danisch, A. Danu, I. Das, P. Das, P. Das, S. Das, S. Dash, S. De, A. De Caro, G. de Cataldo, L. De Cilladi, J. de Cuveland, A. De Falco, D. De Gruttola, N. De Marco, C. De Martin, S. De Pasquale, S. Deb, H.F. Degenhardt, K. R. Deja, L. Dello Stritto, S. Delsanto, W. Deng, P. Dhankher, D. Di Bari, A. Di Mauro, R.A. Diaz, T. Dietel, Y. Ding, R. Divià, D. U. Dixit, Ø. Djuvsland, U. Dmitrieva, J. Do, A. Dobrin, B. Dönigus, O. Dordic, A.K. Dubey, A. Dubla, S. Dudi, M. Dukhishyam, P. Dupieux, T.M. Eder, R.J. Ehlers, V.N. Eikeland, D. Elia, B. Erazmus, F. Ercolessi, F. Erhardt, A. Erokhin, M.R. Ersdal, B. Espagnon, G. Eulisse, D. Evans, S. Evdokimov, L. Fabbietti, M. Faggin, J. Faivre, F. Fan, A. Fantoni, M. Fasel, P. Fecchio, A. Feliciello, G. Feofilov, A. Fernández Téllez, A. Ferrero, A. Ferretti, V.J.G. Feuillard, P. Glässel, J. Kim, J. Kim, J. Kim, M. Kim, S. Kim, T. Kim, S. Kirsch, I. Kisel, S. Kiselev, A. Kisiel, J.L. Klay, J. Klein, S. Klein, C. Klein-Bösing, M. Kleiner, T. Klemenz, A. Kluge, A.G. Knospe, C. Kobdaj, M.K. Köhler, T. Kollegger, A. Kondratyev, N. Kondratyeva, E. Kondratyuk, J. Konig, S.A. Konigstorfer, P.J. Konopka, G. Kornakov, S.D. Koryciak, L. Koska, O. Kovalenko, V. Kovalenko, M. Kowalski, I. Králik, A. Kravčáková, L. Kreis, M. Krivda, F. Krizek, K. Krizkova Gajdosova, M. Kroesen, J.A. Lopez, N.A. Martin,Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, B. Windelband, A. Yuncu, V. Zaccolo, A. Zaman, C. Zampolli, H.J.C. Zanoli, N. Zardoshti, A. Zarochentsev, P. Závada, N. Zaviyalov, H. Zbroszczyk, M. Zhalov, S. Zhang, X. Zhang, Y. Zhang, V. Zherebchevskii, Y. Zhi, D. Zhou, Y. Zhou, J. Zhu, Y. Zhu, A. Zichichi, G. Zinovjev, N. Zurlo [und weitere]
Gesehen am 19.07.2021